Diachronic Investigations of False Friends - Broz, Vlatko (Array, 2008)
A number of internationalisms originating from Latin have different meanings in English from their cognates in other European languages. This paper presents the results of an investigation of words such as actually, eventually, etiquette, fabric, billion, chef, preservative, sensible, sympathetic, biscuit in Oxford English Dictionary. All these words have retained more or less the same meaning in German, Spanish and Croatian (each taken in this research as a representative of three major linguistic branches of the Indo– European language family), whereas English shows a departure from the original meaning. The causes for the shift in meaning are explained through the cognitive mechanisms of metonymy and metaphor and a tentative period is determined when these semantic changes were under way in the course of the development of the English language.